2004
DOI: 10.1002/lia.1055
|View full text |Cite
|
Sign up to set email alerts
|

In search of authenticity: Now more than ever, soft skills are needed

Abstract: In an environment where organizations and their people are experiencing greater and faster change—often highly disruptive change—it's crucial that more emphasis be placed on identifying and developing executives who possess emotional intelligence skills in addition to the more traditional leadership competencies. Among other things, today's leaders need to manage the dynamic tension between a sense of urgency and realistic patience and between optimism and realism and openness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…There were a substantial number of articles indicating that leaders with high levels of EI are substantially concerned for their followers' needs (Akerjordet & Severinsson, ; Bunker & Wakefield, ; ­Delmantoff & Lazarus, , Eason, ; Hayashi, ; Hinchliife, 2010; Hutchinson & Hurley, ; Ingram & Cangemi, ; Mast et al, ; McKee et al, ; Taylor et al, ). Based on this, if leaders have a large concern for their followers and their needs, they are demonstrating the transformational leadership characteristics of empathy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were a substantial number of articles indicating that leaders with high levels of EI are substantially concerned for their followers' needs (Akerjordet & Severinsson, ; Bunker & Wakefield, ; ­Delmantoff & Lazarus, , Eason, ; Hayashi, ; Hinchliife, 2010; Hutchinson & Hurley, ; Ingram & Cangemi, ; Mast et al, ; McKee et al, ; Taylor et al, ). Based on this, if leaders have a large concern for their followers and their needs, they are demonstrating the transformational leadership characteristics of empathy.…”
Section: Resultsmentioning
confidence: 99%
“…Table lists the empirical articles identified that covered EI's relationship to leadership. Within this literature a trend emerged in which most of the articles found in the literature review explained that a leader's EI is directly related to empowering employees as well as having a high level of concern for their needs (Akerjordet & Severinsson, ; Bunker & Wakefield, ; ­Delmantoff & Lazarus, ; Eason, ; Hayashi, ; Hinchliife, 2010; Hutchinson & Hurley, ; Ingram & Cangemi, ; Kreitz, ; Mast et al, ; McKee, Tilin, & Mason, 2012; Taylor, Taylor, & Stoller, ). Fields mentioned in these studies were mainly related to local academic leadership, nursing leadership, library leadership, government, project management, department management, outdoor leadership, and banking.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing the demands of fiscal management and, at the same time, providing effective leadership to employees is difficult in times of uncertainty. 4 More often, priority is given to the financial needs of the institution over the needs of employees.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Snell et al (2002) have found that the failure rate of a project is between 40% and 70% and the major issue causing this failure is the lack of soft skills. Somerset (2001) and Bunker and Wakefield (2004) emphasize that organizational success in the workplace is widely influenced by the soft skills of the workforce. In India, the market's growth needs and increasing demands have led companies to promote people faster than before, however, firms are faced with candidates who do not have the necessary soft skills needed and are not eligible to be moved from a technical position to a managerial postision.…”
Section: F Independent Sample T-tests Per Unitmentioning
confidence: 99%